Metallo-beta-lactamases of Pseudomonas aeruginosa--a novel mechanism resistance to beta-lactam antibiotics. - Dorota Olszańska; Marcin Zórawski; Tomasz Hauschild; Piotr Wieczorek; Paweł Sacha; Elzbieta Tryniszewska (Folia Histochemica et Cytobiologica, 2008)
Since about twenty years, following the introduction into therapeutic of news beta-lactam antibiotics (broad-spectrum cephalosporins, monobactams and carbapenems), a very significant number of new beta-lactamases appeared. These enzymes confer to the bacteria which put them, the means of resisting new molecules. The genetic events involved in this evolution are of two types: evolution of old enzymes by mutation and especially appearance of new genes coming for some, from bacteria of the environment. Numerous mechanisms of enzymatic resistance to the carbapenems have been described in Pseudomonas aeruginosa. The important mechanism of inactivation carbapenems is production variety of b-lactam hydrolysing enzymes associated to carbapenemases. The metallo-beta-enzymes (IMP, VIM, SPM, GIM types) are the most clinically significant carbapenemases. P. aeruginosa posses MBLs and seem to have acquired them through transmissible genetic elements (plasmids or transposons associated with integron) and can be transmission to other bacteria. They have reported worldwide but mostly from South East Asia and Europe. The enzymes, belonging to the molecular class B family, are the most worrisome of all beta-lactamases because they confer resistance to carbapenems and all the beta-lactams (with the exception of aztreonam) and usually to aminoglycosides and quinolones. The dissemination of MBLs genes is thought to be driven by regional consumption of extended--spectrum antibiotics (e.g. cephalosporins and carbapenems), and therefore care must be taken that these drugs are not used unnecessarily.